2022
DOI: 10.1155/2022/5766617
|View full text |Cite|
|
Sign up to set email alerts
|

The Intervention of Music Therapy on Behavioral Training of High-Functioning Autistic Children under Intelligent Health Monitoring

Abstract: Autism is a serious and widespread developmental disorder in children. With the increase of autistic children every year, it is necessary to study a set of effective music therapy activities that can penetrate into life to help autistic children’s rehabilitation training. This paper aims to study the behavioral training of high-functioning autistic children with music therapy intervention under intelligent health monitoring. The autistic children were selected and divided into experimental group and control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The ABA-based treatment program has a significant impact on improving the performance and social adjustment of children with ASD and can be considered by psychologists and counselors as an effective educational program. This integrated study model is derived from ABA and used its three interventions DTT, VM, and VB (He , 2022). Treatments based on applied behaviour analysis are considered as an efficient tool, used with children on the autism spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ABA-based treatment program has a significant impact on improving the performance and social adjustment of children with ASD and can be considered by psychologists and counselors as an effective educational program. This integrated study model is derived from ABA and used its three interventions DTT, VM, and VB (He , 2022). Treatments based on applied behaviour analysis are considered as an efficient tool, used with children on the autism spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on the strategies utilized in assisting children with ASD in the acquisition of language and social skills. Attempts to assess the effectiveness of therapies based on ABA to give useful information to special education instructors dealing with ASD children (He, 2022;McGill &Robinson, 2020). Further, the study has been divided into two groups, one group is provided DTT and VM integrally while the other group is provided VB approach and subsequent aspects of their adequacy and effectiveness in obtaining an improvement in ASD symptoms (He, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%